Metallomics The Science of Biometals (Proteomics, Metabolomics, Interactomics and Systems Biology, 2018)
This book covers the new Omics area, Metallomics. As Metallomics is intrinsically a transdisciplinary area, this book is authored by experts in the field on such diverse topics as Environmental, Nuclear, and Human Metallomics. Within these topics metals play important role, as being part of biomolecules, controlling different biochemical process, being signaling agents, being catalyst of biochemical reactions, among others. This volume demonstrates the importance of more investigation about metals and their interactions with biomolecules. As the knowledge in this field is growing and growing daily, then new challenges concerning studies involving Metallomics is appearing, such as comparative metallomics, speciation metallomics, real-time metallomics, new predictions of metals in biomolecules, metalloprotein databank expansion, interactions between metalloprotein-metalloprotein, among others.